Cerebral Sinus Thrombosis Secondary to SARS-CoV-2 Infection - Mojtaba Khazaei; Kiana Karimi; Parinaz Sedighi; Salman Khazaei (Case Reports in Neurological Medicine)
Coronavirus disease-19 (COVID‐19) is a novel infectious disease and every day we are learning more about its various clinical features and complications. Different studies during the pandemic have shown various neurological manifestations secondary to the infection such as stroke due to cerebral vessel thrombosis. Herein, we presented a 57-year-old man admitted to our hospital with gradual headache, seizure, and decreasing level of consciousness. Three weeks earlier, he was diagnosed with COVID-19 and mild to moderate respiratory problems. Decreased level of consciousness made physicians intubate the patient and initiate mechanical ventilation in the intensive care unit (ICU). Treatment was initiated with phenytoin. Brain CT scan showed right transverse sinus and cortical vein thrombosis with subarachnoid hemorrhage. He received successful anticoagulant therapy, with further improvement in oxygenation, and discharged with a good general condition. This case is important because several neurological complications of COVID-19 should be noticed and managed by appropriate treatment according to the patient’s condition.